"A Name That Recognises You": Local Analysis of Semiotic Dynamics in Semi-Informal Markets in South Africa. Issue 3 (2nd September 2022) - Álvarez-Mosquera, Pedro; Coetzee, Frieda
Abstract: This article explores the linguistic landscape (LL) of semi-informal markets in townships in the Tshwane (Pretoria) Metropolis in South Africa. Similar to other urban African markets, these LLs operate in a context of longstanding and ever-changing multilingualism and multiculturalism. Several indigenous and colonial South African languages are spoken in the area and many traders in the markets are immigrants from other African and South Asian countries. Despite this multilingualism, the public signage is dominated by English. The analysis draws on the semiotic reading of the LL by residents regarding the indexicality of traders' names. Local sign writers provide insight into their instrumental role in shaping the LL of these areas. Furthermore, we draw on the notions of emplacement, spatial scope, and assemblages of semiotics to discuss the significance of mobile phone numbers in unregulated, potentially high-risk activities.